Dilemma in prevention of pertussis infection among infants under six months in China - Xiang Sun (Expert Review of Vaccines)
Introduction Pertussis poses a significant threat to infants under six months due to their immature immune systems, limited maternal antibody protection, and constraints in the vaccination schedule. Despite vaccination efforts, this group remains highly susceptible to severe complications. Addressing these challenges is crucial for improving the health outcomes of infants in China.Areas covered This review examines the primary challenges in preventing pertussis infections among infants under six months in China, focusing on factors such as underdeveloped immune system and inadequate maternal antibody protection. It analyzes limitations in current vaccination strategies and the impact of socio-cultural factors, healthcare resource distribution, and surveillance inadequacies. A comprehensive literature search was conducted to identify potential solutions, including enhancing maternal immunization, adjusting early vaccination strategies, increasing vaccine coverage, and developing new vaccines. The review synthesizes current research findings and data to provide a detailed overview of these issues.Expert opinion Infants under six months are particularly vulnerable to pertussis. Early and effective prevention strategies, such as enhanced maternal immunization and adjusted vaccination schedules, are needed. Increasing vaccine coverage and developing safer, more immunogenic vaccines are essential. Policymakers should prioritize these measures to reduce pertussis incidence and complications among infants in China.